Prevalence of hypertension and associated factors among diabetic patients in Kilimanjaro region, northern Tanzania: A hospital-based cross-sectional study - Julius Mwimo; Faustini C. Kimondo; Innocent B. Mboya (Elsevier, 2023)
Introduction: Hypertension is among the most common non-communicable diseases, being the major cause of premature deaths worldwide. The co-existence of hypertension and diabetes mellitus increases the risk of cardiovascular events and death. Objective: To determine the prevalence of hypertension and associated factors among individuals with type II diabetes mellitus in the Kilimanjaro region, northern Tanzania. Research design and methods: We conducted a cross-sectional study from June to September 2020 among 315 individuals with type II diabetes mellitus aged 18 years and above receiving care from two diabetic clinics in the Kilimanjaro region, northern Tanzania. Participants were selected using a systematic random sampling technique. The WHO Steps Survey for non-communicable diseases was used to collect data and analyzed using SPSS version 20. A multiple logistic regression model was used to estimate the odds ratios (OR) and 95% confidence intervals (CIs) for factors associated with hypertension adjusted for demographic, behavioral, and clinical characteristics. Results: The mean (±SD) age of 315 respondents was 58.62 ± 10.8 years and 58.4% were females. The prevalence of hypertension was 55.2% and was independently associated with older age; 60-69 years (OR = 2.75, 95%CI 1.14-6.64, p-value = 0.02) and ≥70 years (OR = 5.61; 95% CI: 1.65, 19.04), with history of cigarette smoking (OR = 3.98; 95% CI: 1.25, 12.72), and history of ischemic heart disease (OR = 16.86; 95% CI: 2.03, 140.3). Conclusion: More than half of individuals with diabetes in this study had co-existing hypertension, calling for routine and regular checkups of blood pressure at diabetic clinics. Special attention should be given to older individuals (≥60 years), smokers, and those with a history of ischemic heart disease for early prevention and management of adverse complications of diabetes and hypertension.